Carbon baseline as limiting factor in managing environmental sound activities in peatland for reducing greenhouse gas emission - BAMBANG HERO SAHARJO (Society for Indonesian Biodiversity, 2011)
Saharjo BH (2011) Carbon baseline as limiting factor in managing environmental sound activities in peatland for reducing greenhouse gas emission. Biodiversitas 12: 182-186. The total carbon stock in Indonesia was estimated to be around 44.5 Gt or about 53.1% of the total carbon stock in tropical areas. Over 1990-2002, it was estimated that around 3.5 Gt of carbon was released in Sumatra and about 0.81-2.56 Gt was released in Central Kalimantan due to the 1997 fire alone. It was recognized that deforestation, high exploitation of peat and peat fire were behind the huge emissions of Greenhouse Gases in Indonesia. Results of a research conducted in Central Kalimantan peatland, showed that the total carbon stock at logged over area was estimated around 413.972 t ha-1 (0-30 cm depth of peat) and at burnt area was 411.349 t ha-1 (0-30 cm depth of peat). Meanwhile it had been well recognized that most of opened peatlands had been occupied by Acacia crassicarpa and oil palms. Research carried out in East Kalimantan showed that the carbon stock of 25 yearsold oil palm planted on mineral soil was about 180 t ha-1, which is less than that of carbon stock produced by peatland clearance. This indicated that although plants occupied peatland, high Greenhouse Gas emissions were still produced, meaning that global climate change would continue and created high risk impacts.